Breaking the Cycle: The Impact of Hygiene Deficiencies on the Health of the Poor - Sudipta Roy (Emerging Trends in Personalized Medicines, 2025)
Poor sanitation and hygiene present significant health risks, particularly for individuals in low- income communities. Inadequate sanitation systems increase the likelihood of exposure to harmful microorganisms found in contaminated water, food, and environments. This exposure contributes to the spread of waterborne diseases such as cholera, dysentery, and typhoid, along with various gastrointestinal illnesses. Limited access to clean water and soap for handwashing exacerbates these risks, particularly for children, who are especially vulnerable. Beyond the immediate health consequences, poor sanitation has long-term social and economic implications. Frequent illnesses resulting from unsanitary conditions can prevent individuals from working or attending school, diminishing overall productivity and perpetuating cycles of poverty. To address these issues, sustainable solutions are essential, including: Enhanced access to clean water, Reliable sanitation systems, Comprehensive hygiene education programs that promote better community health outcomes, Hygiene Education Materials: To effectively support hygiene education, the following materials can be utilized: Posters and Visual Aids: Handwashing steps, Hygiene routines, Germ cycle charts, Hygiene Kits: Soap, Toothbrushes, Hand sanitizer, Tissues for use at school and home, Interactive Tools: Games, Demonstrations, Visual models that reinforce hygiene lessons, Multimedia Resources: Engaging videos and songs that explain hygiene concepts in an enjoyable manner, Worksheets and Activities: Educational worksheets, Games, Journals promoting hygiene practices, Incorporating these materials into a structured educational program can effectively teach students about personal hygiene, reducing the transmission of illness, and cultivate healthy habits for life.
Keywords: Poor Sanitation; Waterborne Diseases; contaminated environmental resources; hygiene; poverty